2000
DOI: 10.1542/peds.105.1.e6
|View full text |Cite
|
Sign up to set email alerts
|

Biobehavioral Pain Responses in Former Extremely Low Birth Weight Infants at Four Months' Corrected Age

Abstract: Biobehavioral pain responses were similar overall between both groups of infants. Subtle differences were observed in cardiac autonomic responses during the lance period and in behavioral recovery among ELBW infants. Whether these findings represent a long-term effect of early pain experience or a developmental lag in pain response remains unclear. The lack of an overall difference runs counter to previously reported findings of reduced behavioral response in former ELBW infants. biobehavioral pain response, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
3
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(87 citation statements)
references
References 27 publications
7
74
3
3
Order By: Relevance
“…The prevention of pain is important not only because it is an ethical expectation but also because repeated painful exposures can have deleterious consequences. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] These consequences include altered pain sensitivity 5,[7][8][9] (which may last into adolescence 15 ) and permanent neuroanatomic and behavioral abnormalities, as found in animal studies. 5,14 It seems that altered pain sensitivity can be ameliorated if effective pain relief is provided.…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of pain is important not only because it is an ethical expectation but also because repeated painful exposures can have deleterious consequences. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] These consequences include altered pain sensitivity 5,[7][8][9] (which may last into adolescence 15 ) and permanent neuroanatomic and behavioral abnormalities, as found in animal studies. 5,14 It seems that altered pain sensitivity can be ameliorated if effective pain relief is provided.…”
Section: Introductionmentioning
confidence: 99%
“…Stress induced analgesia may also be observed in large trauma victims. In rats it has been found that c-fos expression diminishes when a painful stimulus is applied during stressful conditions (MagalhĂŁes 2003) There are some suppositions that repeated stimuli in the same place may develop altered disseminated responses during pain perception (Oberlander et al 2000, Gibson 2004, Camozzatto et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…NFCS [16] was used to measure infants' facial responses to acute pain. Based on the use of NFCS in previous work [11,25,27] The original NFCS study [16] provided evidence of adequate psychometric properties.…”
Section: Infant Behavioural Pain Measuresmentioning
confidence: 99%
“…In preverbal infants, clinicians and researchers are wholly dependent on proxy judgments by benevolent adult caregivers, posing challenges with notable drawbacks [25,29]. To 'hear' the voice of the infant we must use behavioural measures.…”
Section: Introductionmentioning
confidence: 99%